SINTESIS BIOPROPANOL DARI GLISEROL SEBAGAI BAHAN BAKAR ALTERNATIF - , NINING RAHAYU, Prof. Drs. Jumina, P.Hd. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Synthesis of 1 -propanol from glycerol has been performed. 1 -Propanol was synthesized via several steps i.e. (1) dehydration of glycerol with formic acid by distillation method at 195-260 oC to produce allyl alcohol, (2) activation of Raney-nickel catalyst using 6.5 M NaOH, then isomerization of allyl alcohol catalyzed by activated Raney-nickel with a 5:1 mass ratio at 70 oC for 2 hours to produce propanal, and (3) reduction of propanal with NaBH4 and ethanol at room temperature for 4 hours to produce 1 -propanol. Confirmation of the structure of the resulting compound is carried out by IR spectrometer, GC and GC-MS. Dehydration reaction of glycerol with formic acid produced allyl alcohol in 50% yield. Isomerization reaction of allyl alcohol with Raney-nickel catalyst yielded propanal in 71% yield. Reduction reaction of propanal with NaBH4 produced 1-propanol in 73% yield.